Profound Chemopreventative Effects of a Hydrogen Sulfide-Releasing NSAID in the APCMin/+ Mouse Model of Intestinal Tumorigenesis. - Mark Paul-Clark; Wagdi Elsheikh; Nicholas Kirkby; Melissa Chan; Pallavi Devchand; Terence A Agbor; Kyle L Flannigan; Charlotte Cheadle; Maxim Freydin; Angela Ianaro; Jane A Mitchell; John L Wallace (PLoS ONE)
Nonsteroidal anti-inflammatory drugs have been shown to reduce the incidence of gastrointestinal cancers, but the propensity of these drugs to cause ulcers and bleeding limits their use. H2S has been shown to be a powerful cytoprotective and anti-inflammatory substance in the digestive system. This study explored the possibility that a H2S-releasing nonsteroidal anti-inflammatory drug (ATB-346) would be effective in a murine model of hereditary intestinal cancer (APCMin+ mouse) and investigated potential mechanisms of action via transcriptomics analysis. Daily treatment with ATB-346 was significantly more effective at preventing intestinal polyp formation than naproxen. Significant beneficial effects were seen with a treatment period of only 3-7 days, and reversal of existing polyps was observed in the colon. ATB-346, but not naproxen, significantly decreased expression of intestinal cancer-associated signaling molecules (cMyc, β-catenin). Transcriptomic analysis identified 20 genes that were up-regulated in APCMin+ mice, 18 of which were reduced to wild-type levels by one week of treatment with ATB-346. ATB-346 is a novel, gastrointestinal-sparing anti-inflammatory drug that potently and rapidly prevents and reverses the development of pre-cancerous lesions in a mouse model of hereditary intestinal tumorigenesis. These effects may be related to the combined effects of suppression of cyclooxygenase and release of H2S, and correction of most of the APCMin+-associated alterations in the transcriptome. ATB-346 may represent a promising agent for chemoprevention of tumorigenesis in the GI tract and elsewhere.